Flexible strain sensor material for monitoring shock insulation support as well as preparation method and application of flexible strain sensor material

By using flexible strain sensor materials prepared with modified multi-wall carbon nanotubes and anionic dispersant on the seismic isolation support, the problem of real-time monitoring of the seismic isolation support is solved, efficient and accurate structural health monitoring is achieved, and detection costs are reduced.

CN119842236AActive Publication Date: 2025-04-18KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411913801.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-18
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to realize real-time performance monitoring and damage analysis of earthquake isolation support in service, resulting in insufficient detection accuracy and reliability, and high cost, making real-time data unable to be obtained.

Method used

A flexible strain sensor material is used, which consists of modified multi-wall carbon nanotubes and anionic dispersant, and is prepared by ultrasonic stirring and vulcanization processes to form a conductive network that is uniformly dispersed in the rubber matrix to achieve response monitoring of loads and deformations.

Benefits of technology

It realizes intelligent monitoring of earthquake-isolated bearings, can collect dynamic stress and strain information in real time, accurately determine the degree of damage and service life of the bearings, reduces detection costs and improves monitoring accuracy and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005206368500000011
    Figure HDA0005206368500000011
  • Figure HDA0005206368500000012
    Figure HDA0005206368500000012
Patent Text Reader

Abstract

The invention discloses a flexible strain sensor material for monitoring a shock insulation support and a preparation method and application thereof, and the preparation method comprises the following steps: S1, mixing lauryl sodium sulfate, tetradecyl trimethyl ammonium bromide and a conductive filler in an organic solvent, after fully and uniformly mixing, heating and volatilizing to remove the organic solvent to obtain a conductive nano filler; s2, mixing: mixing the conductive nanofiller with methyl vinyl silicone rubber, silicon dioxide and a vulcanizing agent according to a mass ratio, and mixing to obtain a mixture; s3, vulcanization: the mixture is taken and vulcanized in two stages, the vulcanization temperature in the second stage is 20-30 DEG C higher than the vulcanization temperature in the first stage, and the flexible strain sensor material is obtained. The prepared sensor material is stretchable, high in sensitivity, good in mechanical property, short in response time and stable in resistance / response signal, and is particularly suitable for real-time structural health monitoring of a shock insulation support under large deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber materials and strain sensing technology, and in particular to a flexible strain sensor material for monitoring a seismic isolation bearing, and a preparation method and application thereof. Background Art

[0002] Earthquake is a natural disaster that seriously threatens the safety of human life and property. Therefore, countries around the world are committed to doing a good job in engineering earthquake resistance and disaster reduction, and are committed to improving the earthquake resistance level of construction projects and improving the earthquake resistance of construction projects. The use of seismic isolation technology and seismic isolation bearings can isolate or consume the energy of seismic waves, which is currently the most effective seismic resistance measure. Foundation seismic isolation technology is to use a flexible connection between the building superstructure and the foundation to set up a sufficiently safe seismic isolation system. Due to the "seismic isolation" and "shock absorption" effects of the seismic isolation layer, the superstructure moves approximately horizontally during an earthquake, and the structural response is only equivalent to 1 / 4-1 / 8 of the case without seismic isolation, thereby "isolating" the earthquake. Among many seismic isolation systems, seismic isolation rubber bearings are the mainstream of world research and application. Seismic isolation bearings are a device used for seismic isolation of building structures. Their main function is to reduce the impact of earthquakes on buildings by adding a seismic isolation layer between the foundation and the superstructure of the building. The working principle of seismic isolation bearings is mainly based on two aspects: one is to absorb seismic energy through the deformation of elastic materials; the other is to dissipate seismic energy through sliding or damping mechanisms. Specifically, when an earthquake occurs, the energy generated by the ground movement is first absorbed and dissipated by the seismic isolation layer, and only a small part of the energy is transmitted to the upper structure through the seismic isolation bearings, thereby greatly reducing the seismic effect on the building. Various laminated rubber bearing seismic isolation houses currently used at home and abroad have been tested by many strong earthquakes and have good seismic isolation effects and significant earthquake resistance.

[0003] However, when the seismic isolation bearings are often in a high-load working environment of "continuous small earthquakes and occasional strong earthquakes", the bearings are severely damaged and have a short service life; in addition, the seismic isolation bearings are mainly made of rubber materials, and the aging and failure of rubber will also accelerate the fatigue and damage of the bearings. It can be said that the service performance of seismic isolation bearings in high-intensity earthquake zones directly determines the health of the engineering structure. Therefore, regular inspections of seismic isolation bearings are very important to ensure their normal performance. Inspection items include seismic isolation bearings, isolation joints, flexible connections, tensile devices, etc.; inspection contents include instrumental measurements of horizontal deformation and vertical compression deformation of bearings, as well as observation and inspection of other items.

[0004] However, most experimental test methods at home and abroad are only for seismic isolation bearings before use. The real-time performance and damage degree analysis of bearings during service can only rely on theoretical simulation, which is not accurate and reliable enough. For situations where simulation methods cannot be used for analysis, the bearings must be removed from the building for testing, which is a large project with low efficiency and very high cost, and real-time data cannot be obtained. Taking a large building as an example, the seismic isolation bearings of the building have been in service for more than 10 years. During this period, it has experienced 6 earthquakes below magnitude 5 on the Richter scale. The damage of some bearings needs to be evaluated urgently, but the cost of disassembly and inspection of a single bearing exceeds 50,000 yuan, and the damage degree of different bearings is different. It is not necessary to disassemble and inspect all bearings. If the performance of seismic isolation bearings can be monitored in real time under service status and the dynamic stress and strain information of bearings can be obtained, the damage degree of each bearing can be determined in time and accurately, and the service life can be evaluated; at the same time, the degree of damage to the building by seismic waves can be analyzed, and a comprehensive analysis and early warning of the safety status of the engineering structure can be achieved. Therefore, real-time monitoring of bearing service performance has become a bottleneck in the development of seismic isolation technology and a problem that needs to be solved in the current field of disaster prevention and mitigation.

[0005] One of the core issues of structural health monitoring technology for seismic isolation bearings is intelligent sensing technology. Currently, the widely used structural health monitoring sensors are mainly made of inorganic non-metallic materials such as fiber gratings and piezoelectric ceramics. Such materials are brittle, weak in damage resistance, poor in durability and processability, high in maintenance costs, and low in service life. The structural and functional characteristics of rubber seismic isolation bearings themselves determine that the sensing material must have the characteristics of large deformation, damage resistance, long life, and high sensitivity. Ordinary inorganic non-metallic intelligent materials are no longer applicable. This problem is more prominent in high-intensity earthquake zones, which is why real-time monitoring of seismic isolation bearings has not yet been achieved. Therefore, the research and development of new intelligent sensing materials is urgent.

[0006] Multi-walled carbon nanotubes have excellent physical and chemical properties, and their unique microstructure has obvious advantages for constructing molecular conductive networks. Multi-walled carbon nanotubes are mixed with anionic and cationic dispersants such as sodium dodecyl sulfate and tetradecyl trimethyl ammonium bromide by ultrasonic stirring, so that a stable charge layer is formed on the surface of multi-walled carbon nanotubes. Electrostatic repulsion is generated to prevent the aggregation of multi-walled carbon nanotubes, promote the uniform dispersion of conductive nanofillers in the rubber matrix, and construct a conductive network with large deformation capacity inside the material. According to the principle of tunnel effect, the resistivity of the conductive network will change synchronously with the deformation, realizing the response monitoring of load and deformation. This resistance / strain response material has been widely studied in the fields of biomedicine and mechanical manufacturing due to its good anti-destructive and processability. The core material of the seismic isolation bearing is rubber. If intelligent sensing materials suitable for load and deformation monitoring of seismic isolation bearings can be designed and prepared, the compatibility problem between sensors and seismic isolation materials can be completely solved. It is the only choice for new sensing materials and is of great significance to the development of structural health monitoring technology. Summary of the invention

[0007] The object of the present invention is to provide a flexible strain sensor material for monitoring seismic isolation bearings and a preparation method and application thereof in view of the above-mentioned problems.

[0008] In order to achieve its purpose, the present invention adopts the following technical solution:

[0009] A first aspect of the present invention provides a method for preparing a flexible strain sensor material for monitoring a seismic isolation bearing, comprising the following steps:

[0010] S1. Preparation of conductive nanofillers:

[0011] Sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and a conductive filler are mixed in an organic solvent, and after being fully mixed, the organic solvent is removed by volatilization at a high temperature to obtain a conductive nanofiller;

[0012] The mass ratio of sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and conductive filler is 0-5:0-1.2:0.8-1.2;

[0013] S2. Mixing

[0014] The conductive nanofiller prepared in step S1 is mixed with methyl vinyl silicone rubber, silicon dioxide, and a vulcanizing agent in a mass ratio of 12-16:350-450:6-10:3-5, and kneaded to obtain a mixture;

[0015] S3, vulcanization:

[0016] The mixed material prepared in step S2 is vulcanized in two stages, wherein the vulcanization temperature in the second stage is 20 to 30° C. higher than that in the first stage, to obtain the flexible strain sensor material.

[0017] Preferably, the organic solvent is ethyl acetate or tetrahydrofuran or acetone;

[0018] The conductive filler is selected from multi-walled carbon nanotubes or conductive carbon black;

[0019] The vulcanizing agent is selected from one or more of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl perbenzoate, and dibenzoyl peroxide.

[0020] In step S1, the mass ratio of sodium dodecyl sulfate, tetradecyltrimethylammonium bromide and conductive filler is 1-4:0.8-1.2:0.8-1.2 or 1-3:0.9-1.1:0.9-1.1;

[0021] In step S1, sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and a conductive filler are mixed in an organic solvent, ultrasonically stirred to mix evenly, and the organic solvent is removed by volatilization by heating to obtain a conductive nanofiller; wherein the volume ratio of the sum of the mass of sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and the conductive filler to the organic solvent is 0.1-1 g:100-1000 ml;

[0022] The ultrasonic stirring conditions are: ultrasonic frequency of 100-150 Hz, stirring rate of 450-600 rpm, and ultrasonic stirring mixing for 2-4 hours;

[0023] Preferably, magnetic stirring is performed before ultrasonic stirring, and the magnetic stirring condition is stirring at a stirring rate of 450 to 600 rpm for 30 to 60 min;

[0024] The organic solvent is ethyl acetate, and the temperature is raised to 50-70° C. to remove the ethyl acetate and obtain a conductive nano filler.

[0025] In step S2, the conductive nano filler is mixed with methyl vinyl silicone rubber, silicon dioxide, and a vulcanizing agent in a mass ratio of 13-15:380-420:7-9:3-5 or 14:400:8:4;

[0026] The mixing temperature is 40-60°C, the roller distance is 0.5-1mm, the speed is 20-35rpm, and the mixing process is 40-60min.

[0027] In step S3, the first stage of vulcanization has a vulcanization temperature of 150-170°C, a time of 10-20 min, and a pressure of 10-20 MPa, preferably a vulcanization temperature of 160-170°C, a time of 10-15 min, and a pressure of 10-15 MPa;

[0028] Then the second stage vulcanization treatment is carried out, the vulcanization temperature is 180-200°C, and the time is 2-4 hours.

[0029] In step S3, the first stage vulcanization is carried out on a flat plate vulcanizer, and the second stage vulcanization is carried out in an oven.

[0030] The vinyl content of the methyl vinyl silicone rubber is 0.18%, and the molecular weight is 6.2×10 5 g / mol;

[0031] The multi-walled carbon nanotubes are 10-20 μm long, 4-6 nm in diameter, and have a specific surface area of ​​500-700 m 2 / g.

[0032] The nano-silicon dioxide has a particle size of 7-40 nm and a specific surface area of ​​300 m 2 / g.

[0033] A second aspect of the present invention provides a flexible strain sensor material, which is prepared by any of the preparation methods described above.

[0034] A third aspect of the present invention provides use of the above-mentioned flexible strain sensor material in preparing a flexible strain sensor.

[0035] Preferably, the flexible strain sensor material is prepared into a flexible sensor for structural health monitoring of seismic isolation bearings.

[0036] The beneficial effects of the present invention are:

[0037] (1) By assembling the flexible strain sensor material of the present invention with a seismic isolation bearing, the compatibility of the flexible strain sensor material with the rubber seismic isolation material and the resistance / strain response characteristics are fully utilized, so that the bearing has both seismic isolation function and strain signal collection function, realizes the intelligence of the seismic isolation bearing, and promotes the development of seismic isolation bearing structural health monitoring technology.

[0038] (2) Although there are many research reports on smart sensors, their application in the field of civil engineering and seismic isolation technology is still blank. This project aims to realize the service performance monitoring of rubber seismic isolation bearings, and specifically innovates the preparation and application of flexible smart sensors to open up new areas for the application of nanocarbon materials.

[0039] (3) Compared with traditional commercial conductive fillers, the present invention uses self-assembled anionic and cationic dispersants to modify multi-walled carbon nanotubes. The conductive fillers modified by the anionic and cationic dispersants can be evenly dispersed in the rubber matrix, and can form a stable charge layer on the surface of the multi-walled carbon nanotubes, thereby producing a significant electrostatic repulsion effect and effectively inhibiting the agglomeration of the multi-walled carbon nanotubes. This self-assembly method not only significantly improves the uniform dispersion of the conductive nanofiller in the rubber matrix, but also promotes the reconstruction stability of the conductive network inside the material, thereby giving the rubber composite material excellent deformation ability, mechanical properties and conductive properties. The rubber composite material prepared by the method of the present invention is used as a sensor material, and has lower volume conductivity and more stable resistance / strain response signal acquisition capabilities than flexible sensors prepared from commercial multi-walled carbon nanotubes.

[0040] (4) The appropriate ratio of anionic and cationic dispersants can make multi-walled carbon nanotubes more compatible with the rubber matrix, enhance the interfacial bonding strength of the composite material, and thus have good dispersion in the rubber matrix, thereby achieving a significant improvement in the performance of the final product.

[0041] The present invention prepares a flexible strain sensor material that is stretchable, highly sensitive, has good mechanical properties, fast response time, and stable resistance / response signal in a low-cost, high-efficiency, and pollution-free manner. The material can undergo synchronous deformation coordination with the isolation bearing and output a response monitoring signal, thereby being suitable for real-time structural health monitoring of the isolation bearing under large deformation, providing strong technical support for the structural health monitoring of large components using intelligent sensing monitoring technology, and having broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a process flow chart for preparing the flexible strain sensor material of the present invention.

[0043] Figure 2 This is a diagram showing the actual conditions of the flexible strain sensor material of Example 4 under stretching, torsion, and bending.

[0044] Figure 3 The SEM microscopic morphology images of the flexible strain sensors of Comparative Example 2 and Example 4 are shown.

[0045] Figure 4 is the response time of the flexible strain sensor material of Example 4.

[0046] Figure 5 This is the monitoring response signal of the flexible strain sensor material of Example 4 to the seismic isolation bearing. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0048] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0049] Example

[0050] The raw materials are:

[0051] Anionic dispersant sodium dodecyl sulfate (SDS, CAS No. 151-21-3), cationic dispersant tetradecyltrimethylammonium bromide (TTAB, CAS No. 1119-97-7), multi-walled carbon nanotubes (MWCNT), ethyl acetate, methyl vinyl silicone rubber (VMQ), nano-silica, diisopropylbenzene peroxide (curing agent DCP).

[0052] Among them, the vinyl content of methyl vinyl silicone rubber is 0.18%, and the molecular weight is 6.2×10 5 g / mol. Multi-walled carbon nanotubes are 10-20 μm long, 4-6 nm in diameter, and have a specific surface area of ​​500-700 m 2 / g.

[0053] Nano-silicon dioxide particle size 7-40nm, specific surface area 300m 2 / g.

[0054] The preparation method of the flexible strain sensor material for monitoring the seismic isolation support of the present invention (process flow chart as shown in FIG. Figure 1 ), follow the steps below:

[0055] S1. Preparation of conductive nanofillers:

[0056] The anionic and cationic dispersants (sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide) and multi-walled carbon nanotubes were mixed in ethyl acetate using a magnetic stirrer, and stirred at a stirring rate of 450 rpm for 30 minutes at room temperature to obtain a conductive filler suspension. The beaker containing the conductive filler suspension was then placed in an ultrasonic cleaner, a stirrer was installed above the beaker, the stirring head was inserted into the beaker, the ultrasonic frequency was set to 100 Hz, the temperature was 20°C, the stirring rate of the stirrer was 450 rpm, and ultrasonic stirring was performed for 2 hours. After the end, the temperature was raised to 50°C to remove the ethyl acetate, and a conductive nanofiller (black powder) was obtained.

[0057] This process can form a stable charge layer on the surface of multi-walled carbon nanotubes, thereby producing a significant electrostatic repulsion effect, effectively inhibiting the agglomeration of multi-walled carbon nanotubes. Then, in the next step, they can be evenly dispersed in methyl vinyl silicone rubber.

[0058] S2. Mixing to prepare conductive nanocomposite:

[0059] The conductive nanofiller prepared in step S1 was uniformly mixed with methyl vinyl silicone rubber, silicon dioxide and diisopropylbenzene peroxide in a double-roll mill, wherein the mixing temperature was 60° C., the roller distance was 1 mm, the speed was 20 rpm, and the mixing process was 40 min to obtain an unvulcanized conductive nanomixture.

[0060] This process uses the shear force generated by the double-roll mill to evenly disperse the filler in the methyl vinyl silicone rubber to form a three-dimensional conductive network, enabling it to collect signals for monitoring seismic isolation bearings under large deformations.

[0061] S3, vulcanization

[0062] S3.1. First stage vulcanization: The conductive nanocomposite prepared in step S2 is placed in a flat vulcanizer and vulcanized at a temperature of 170° C., a pressure of 10 MPa, and a time of 10 min to obtain a product after the first stage vulcanization.

[0063] In the first stage of vulcanization, dicumyl peroxide is decomposed into free radicals through high temperature, which triggers the breakage of the vinyl double bonds in the methyl vinyl silicone rubber, and generates new free radicals to cross-link the molecular chains in the rubber to form a cross-linked structure.

[0064] S3.2, second stage vulcanization: put the conductive nano-rubber composite material that has completed the first stage vulcanization into an oven and vulcanize it at a temperature of 200°C for 4 hours to obtain a block-shaped conductive nano-rubber composite material, which is the flexible strain sensor material.

[0065] In the second stage of vulcanization, free radicals are initiated to form cross-linking points at high temperature, which further increases the degree of cross-linking and improves the mechanical properties, high temperature resistance, elasticity and chemical stability of the flexible smart sensor.

[0066] According to the above method, the conductive nano-rubber composite materials of Examples 1-4 were prepared. The specific raw material proportions of each example are shown in Table 1:

[0067] Table 1

[0068] Example / Raw Materials Example 1 Example 2 Example 3 Example 4 SDS / g 0 0.16 0.32 0.48 TTAB / g 0 0.16 0.16 0.16 MWCNT / g 0.16 0.16 0.16 0.16 Ethyl acetate / ml 500 500 500 500 Conductive nanofiller / g 0.14 0.14 0.14 0.14 VMQ / g 4 4 4 4 Silicon dioxide / g 0.08 0.08 0.08 0.08 Curing agent DCP / g 0.04 0.04 0.04 0.04

[0069] Comparative Example 1 (using the same raw materials as the present invention, but different processes)

[0070] The raw materials and dosage of Example 4 of the present invention are used, but the preparation process adopts the existing technology process: methyl vinyl silicone rubber, commercial multi-walled carbon nanotubes, sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide, silicon dioxide, and diisopropyl peroxide are directly put into an internal mixer for mixing, and the set temperature is 70°C, the speed is 80rpm, the roller distance is 1mm, and the time is 30min. Then put it into a flat plate vulcanizer and vulcanize it at a pressure of 15MPa, a temperature of 160°C, and a time of 15min.

[0071] Comparative Example 2 (using different raw materials and the same process as the present invention)

[0072] Different raw materials from those in Example 4 were used. Specifically, the filler included 100 parts of methyl vinyl silicone rubber, 10 parts of conductive carbon black, 300 ml of tetrahydrofuran, 5 parts of silicon dioxide, and 2 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (curing agent bis-25). The flexible strain sensor material was prepared according to the preparation process of Example 4.

[0073] The preparation process is as follows: conductive carbon black is mixed with tetrahydrofuran, stirred for 30 minutes at room temperature by a magnetic stirrer at a stirring rate of 450rpm to obtain a conductive filler suspension; then the conductive filler suspension is placed in an ultrasonic cleaner, ultrasonically stirred for 2 hours at an ultrasonic frequency of 100Hz, a temperature of 20°C, and an ultrasonic stirring rate of 450rpm, and the temperature is raised to 50°C to remove tetrahydrofuran to obtain a conductive black powder filler. Methyl vinyl silicone rubber is placed in a double-roll open mill and then a conductive black powder filler, silicon dioxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are placed and mixed uniformly at a temperature of 60°C, a roller distance of 1mm, a speed of 20rpm, and a time of 40min to obtain an uncured conductive nano-mixture. The uncured conductive nano-mixture was placed in a flat-plate vulcanizer for the first stage of vulcanization. The vulcanization conditions were temperature 170°C, pressure 10 MPa, and time 10 min to obtain the product after the first stage of vulcanization. The product was then placed in an oven at 200°C for 4 hours for the second stage of vulcanization to obtain a flexible strain sensor material.

[0074] Performance Testing

[0075] The performance of the prepared flexible strain sensor material is tested.

[0076] (1) Volume conductivity: The volume conductivity of the conductive nano rubber material is tested according to the GT / T1692-2008 standard. First, the sample is cut into a standard sample of 40mm×10mm×1mm (the surface is cleaned with anhydrous ethanol), and the resistance value of the sample in the unstrained state is measured using a Keysight 34465A digital multimeter. The average resistance value within 1s of the digital multimeter is collected, and the average value is taken for each group of 3 test strips. The volume conductivity formula is defined as:

[0077]

[0078] In formula (1), σ is the volume conductivity (S / m), ρ is the volume resistivity of the material (Ω·m), R is the volume resistance (Ω), L is the length of the sample (m), and S is the cross-sectional area (m 2 ).

[0079] (2) Sensitivity test: Clamp the two ends of the conductive nano rubber material on an electronic universal testing machine, take a wire, connect one end of the wire to the conductive nano rubber material, and the other end of the wire to a digital multimeter. Set the strain through the universal testing machine. After a single stretching cycle, the maximum resistance value is transmitted to the computer through the digital multimeter, and then the sensitivity is calculated through the resistance and strain according to formula (2).

[0080] Sensitivity calculation method: Formula (2) is used to evaluate the sensitivity of the composite material:

[0081] GF=(ΔR / R0) / ε Formula (2)

[0082] In formula (2), ε is strain. ΔR / R0, ΔR=R-R0, where R0 is the initial resistance and R is the test resistance.

[0083] (3) Test method of resistance / strain response signal: The conductive nano rubber material is cut into strips of 40 mm × 40 mm × 1 mm, the sample is fixed on an electronic universal testing machine for a cyclic loading-unloading test, and the change of the resistance / strain response signal is recorded with a digital multimeter.

[0084] (4) Mechanical properties test method: According to GB / T528-2009, the mechanical properties of dumbbell-shaped standard conductive nano-rubber material specimens were measured using an electronic universal testing machine (DDL10) at a tensile rate of 200 mm / min. -1 , and take the average value of 3 groups of experimental data.

[0085] The performance test results are shown in Table 2.

[0086] Table 2: Flexible strain sensor material performance results

[0087] Example / Comparative Example Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Example 4 Volume conductivity (S / m) 0.42 0.18 0.07 0.04 <![CDATA[5.37×10 -5 ]]> <![CDATA[6.48×10 -6 ]]> Sensitivity 13.06 48.69 57.69 87.28 210.61 397.21 Tensile strength(MPa) 1.62 4.68 2.33 3.55 5.47 8.17 Elongation at break (%) 221.45 363.42 298.11 321.78 426.79 544.77

[0088] (5) Response time detection

[0089] The flexible strain sensor material of Example 4 was fixed on an electronic universal testing machine, and a cyclic stretch-unloading test was set on the electronic universal testing machine. The two ends of the wire were connected to the sensor and a digital multimeter respectively, and the cyclic stretch-unloading output signal of the sensor was transmitted to a computer to obtain a cyclic resistance / strain signal graph. The time between two adjacent cycles was the response time. The test results are shown in FIG. Figure 4 As shown, the flexible strain sensor material of the present invention can be used as a sensor to quickly reflect the deformation state and collect deformation characteristics in time, and is very suitable for application in seismic isolation bearing structure health monitoring.

[0090] Figure 2 This is a diagram showing the actual conditions of the flexible strain sensor material of Example 4 under stretching, torsion, and bending.

[0091] It can be seen from the various embodiments and comparative examples that the volume conductivity of each embodiment is significantly reduced compared with comparative example 1 or comparative example 2. In particular, the volume conductivity of embodiment 4 using the same filler is more significantly reduced than that of comparative example 1. Comparative example 1 directly mixes all the raw materials for banburying, while embodiment 4 first mixes the conductive nanofiller raw materials for self-assembly through magnetic stirring and ultrasonic mixing. This process can form a stable charge layer on the surface of multi-walled carbon nanotubes, thereby producing a significant electrostatic repulsion effect, effectively inhibiting the agglomeration of multi-walled carbon nanotubes, and then in the next step, it can be evenly dispersed in methyl vinyl silicone rubber to prepare conductive nanofillers. Self-assembly not only significantly improves the uniform dispersion of conductive nanofillers in the rubber matrix, but also promotes the reconstruction stability of the conductive network inside the material, thereby giving the composite material excellent deformation ability and conductive properties. The rubber composite material product finally obtained can reduce the volume conductivity to the greatest extent.

[0092] All embodiments can achieve good sensitivity, and compared with Comparative Example 1 or Comparative Example 2, the sensitivity is improved to varying degrees.

[0093] The tensile strength and elongation at break are mainly related to the dispersion of the conductive nanofiller in the matrix. Comparative Example 1 does not use self-assembled conductive nanofillers, and the tensile strength and elongation at break of the rubber composite material obtained are relatively low. However, the tensile strength and elongation at break of Example 4 are significantly improved.

[0094] The appropriate ratio of anionic and cationic dispersants can make the multi-walled carbon nanotubes more compatible with the rubber matrix, enhance the interfacial bonding force of the composite material, and thus have good dispersibility in the rubber matrix. In Examples 1-4, the mass ratio of sodium dodecyl sulfate to tetradecyl trimethyl ammonium bromide in Example 4 is 3:1, which is greater than the mass ratio of sodium dodecyl sulfate to tetradecyl trimethyl ammonium bromide in Example 1-3. The product performance of Example 4 is better than that of Examples 1-3.

[0095] The SEM microscopic morphology of the materials of Comparative Example 2 and Example 5 ( Figure 3 ) It can be seen that the conductive filler of Comparative Example 2 has serious agglomeration in the rubber matrix, which hinders the continuity of the conductive filler in the rubber matrix. The self-assembled conductive filler of Example 5 has good dispersion in the rubber matrix, which is also an important factor in obtaining low volume conductivity, high sensitivity, good mechanical properties, and stable resistance / strain response signals.

[0096] Through the method of the present invention, in combination with a specific mass ratio of anion and cation dispersants and multi-walled carbon nanotubes and methyl vinyl silicone rubber, a flexible strain sensor material with low volume conductivity, high sensitivity and good mechanical properties can be produced. In addition, the innovative ratio of the raw materials of the present invention enables the flexible strain sensor material itself to have a better resistance / response signal, which is more conducive to real-time structural health monitoring of the isolation bearing. At the same time, the flexible intelligent sensor can overcome the defects of traditional strain sensors such as brittleness, low sensitivity and narrow monitoring range. The resistance / response signal output during the monitoring process cooperates with the perfect deformation of the isolation bearing to obtain the health status of the isolation bearing in real time.

[0097] Application Example 1

[0098] The flexible strain sensor material prepared in Example 4 was cut into blocks of 40×10×1mm, and the cut flexible strain sensor was attached to the building lead core seismic isolation rubber bearing in the laboratory of this research team using special silicone rubber glue. One end of the wire was attached to the sensor material with strong tape, and the other end of the wire was connected to a digital multimeter. When the building lead core rubber bearing deformed, the sensor was deformed, and the sensor deformation caused the resistance to change. The real-time resistance / strain response signal was output on the computer, thereby evaluating the deformation degree of the building lead core rubber bearing, so as to monitor the building lead core rubber bearing. When the rubber bearing deformed greatly under certain experimental conditions, the sensor was deformed greatly, resulting in a significant change in the resistance / response signal, indicating that the rubber bearing was damaged or aged.

[0099] The entire test process was carried out on a shearing machine, with the working conditions of frequency: 0.05-0.1Hz, deformation displacement: 20-80mm, pressure: 10MPa-25MPa. Deformation direction: bidirectional shear deformation. The test results are as follows Figure 5 As shown, as the rubber bearing deforms, the sensor can capture it with high sensitivity and stably output resistance / strain response signals, and the detection results are accurate and reliable.

[0100] Most of the isolation bearings currently on the market are rubber bearings. The flexible strain sensor material prepared by the present invention has a rubber matrix, which can solve the compatibility problem with rubber isolation bearings. At the same time, the flexible strain sensor has high sensitivity, stable resistance / strain response signal output of the deformation of the isolation bearing, and excellent deformation ability, which can achieve perfect coordinated deformation with the isolation bearing. In addition, since the isolation bearings are often in harsh environments, compared with the fragility, low sensitivity, and poor aging resistance of traditional strain sensors, which cannot perform real-time monitoring of the isolation bearings under large deformation, the flexible strain sensor material of the present invention is particularly suitable for real-time monitoring of the structural health of the isolation bearings. The sensor of the present invention is used to monitor the isolation bearings in real time, and there is no need to disassemble each bearing and take it back to the laboratory for testing, which greatly saves manpower, material resources and testing costs.

Claims

1. A method for preparing a flexible strain sensor material for monitoring a seismic isolation support, characterized in that: The steps include: S1. Preparation of conductive nanofillers: Sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and a conductive filler are mixed in an organic solvent, and after being fully mixed, the organic solvent is removed by volatilization at a high temperature to obtain a conductive nanofiller; The mass ratio of sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and conductive filler is 0-5:0-1.2:0.8-1.2; S2. Mixing The conductive nanofiller prepared in step S1 is mixed with methyl vinyl silicone rubber, silicon dioxide, and a vulcanizing agent in a mass ratio of 12-16:350-450:6-10:3-5, and kneaded to obtain a mixture; S3, vulcanization: The mixed material prepared in step S2 is vulcanized in two stages, wherein the vulcanization temperature in the second stage is 20 to 30° C. higher than that in the first stage, to obtain the flexible strain sensor material.

2. The preparation method according to claim 1, characterized in that: The organic solvent is ethyl acetate or tetrahydrofuran or acetone; The conductive filler is selected from multi-walled carbon nanotubes or conductive carbon black; The vulcanizing agent is selected from one or more of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl perbenzoate, and dibenzoyl peroxide.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of sodium dodecyl sulfate, tetradecyltrimethylammonium bromide and conductive filler is 1-4:0.8-1.2:0.8-1.2 or 1-3:0.9-1.1:0.9-1.1; In step S1, sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and a conductive filler are mixed in an organic solvent, ultrasonically stirred to mix evenly, and the organic solvent is removed by volatilization by heating to obtain a conductive nanofiller; wherein the volume ratio of the sum of the mass of sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide and the conductive filler to the organic solvent is 0.1-1 g:100-1000 ml; The ultrasonic stirring conditions are: ultrasonic frequency of 100-150 Hz, stirring rate of 450-600 rpm, and ultrasonic stirring mixing for 2-4 hours; Preferably, magnetic stirring is performed before ultrasonic stirring, and the magnetic stirring condition is stirring at a stirring rate of 450 to 600 rpm for 30 to 60 min; The organic solvent is ethyl acetate, and the temperature is raised to 50-70° C. to remove the ethyl acetate and obtain a conductive nano filler.

4. The preparation method according to claim 1, characterized in that: In step S2, the conductive nano filler is mixed with methyl vinyl silicone rubber, silicon dioxide, and a vulcanizing agent in a mass ratio of 13-15:380-420:7-9:3-5 or 14:400:8:4; The mixing temperature is 40-60°C, the roller distance is 0.5-1mm, the speed is 20-35rpm, and the mixing process is 40-60min.

5. The preparation method according to claim 1, characterized in that: In step S3, The first stage of vulcanization has a vulcanization temperature of 150-170°C, a time of 10-20 min, and a pressure of 10-20 MPa. The preferred vulcanization temperature is 160-170°C, a time of 10-15 min, and a pressure of 10-15 MPa. Then the second stage vulcanization treatment is carried out, the vulcanization temperature is 180-200°C, and the time is 2-4 hours.

6. The preparation method according to claim 5, characterized in that: In step S3, the first stage vulcanization is carried out on a flat plate vulcanizer, and the second stage vulcanization is carried out in an oven.

7. The preparation method according to claim 2, characterized in that: The vinyl content of the methyl vinyl silicone rubber is 0.18%, and the molecular weight is 6.2×10 5 g / mol; The multi-walled carbon nanotubes are 10-20 μm long, 4-6 nm in diameter, and have a specific surface area of ​​500-700 m 2 / g. The nano-silicon dioxide has a particle size of 7-40 nm and a specific surface area of ​​300 m 2 / g.

8. A flexible strain sensor material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the flexible strain sensor material according to claim 8 in preparing a flexible strain sensor.

10. The use according to claim 8, characterized in that: The flexible strain sensor material is prepared into a flexible sensor for structural health monitoring of seismic isolation bearings.

Citation Information

Patent Citations

  • Conductive silicone rubber with high elastic resilience and preparation method thereof

    CN103937258A

  • Clay / rubber nano composite material prepared from compound modified clay

    CN104371152A

  • Sensor material for monitoring health condition of ballastless track plate of high-speed railway in real time and preparation method of the sensor material

    CN111732836A

  • Method for preparing graphene / carbon nanotube composite material

    CN116789110A

  • Method for preparing carbon nanotube solution

    CN116803902A